2020
DOI: 10.3390/ijms21145135
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2-b]pyrazole-7-Carboxamide Derivative Induces Differentiation-Coupled Apoptosis of Immature Myeloid Cells Such as Acute Myeloid Leukemia and Myeloid-Derived Suppressor Cells

Abstract: Chemotherapy-induced differentiation of immature myeloid progenitors, such as acute myeloid leukemia (AML) cells or myeloid-derived suppressor cells (MDSCs), has remained a challenge for the clinicians. Testing our imidazo[1,2-b]pyrazole-7-carboxamide derivative on HL-60 cells, we obtained ERK phosphorylation as an early survival response to treatment followed by the increase of the percentage of the Bcl-xlbright and pAktbright cells. Following the induction of Vav1 and the AP-1 complex, a driver of cellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…After 24 h treatment, cells were washed with PBS and harvested in Accuzo (Bioneer, Daedeok-gu, Daejeon, Korea) and stored at −80 °C. The RNA was isolated, as described previously [ 79 ]. Briefly, RNA was isolated with the Direct-zol RNA Miniprep Kit (ZymoResearch, Irvine, CA, USA), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h treatment, cells were washed with PBS and harvested in Accuzo (Bioneer, Daedeok-gu, Daejeon, Korea) and stored at −80 °C. The RNA was isolated, as described previously [ 79 ]. Briefly, RNA was isolated with the Direct-zol RNA Miniprep Kit (ZymoResearch, Irvine, CA, USA), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The cell cycle distribution and pγ-H2AX content were assayed simultaneously within one tube. The cell cycle and the Sub-G1 fraction were assayed as described previously with some modifications [ 29 ]. Briefly, the U251 cells (2 × 10 5 ) were plated in 6-well dishes (Corning Life Sciences) and were irradiated with 2 Gy, 5 Gy or were left untreated.…”
Section: Methodsmentioning
confidence: 99%
“…Primitive AML cells with sustained self-renewal generally include the early stem/progenitors CD34 + CD38 − LSCs and CD34 + CD38 + LPCs. Having demonstrated the potential of ouabain in targeting primitive AML cells, we next established two study models to specifically determine the effects of ouabain on LSC and LPC death and differentiation, as previous studies reported that the differentiation of AML cells by certain stimuli could induce apoptosis [ 36 , 37 ]. In study model 1, LSCs and LPCs from AML KG-1 cells, that reached a ratio of 1:1 as described in methods section, were cultured in regular AML medium to allow the change in dynamics of LSCs and LPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiation therapy, i.e., all-trans retinoic acid (ATRA) and arsenic trioxide, has been shown to be an effective treatment for acute promyelocytic leukemia (APL), a distinct AML subtype characterized by the expression of the PML/RARA fusion protein [ 23 ]. Previous studies reported that the induction of AML differentiation could sometimes be accompanied by apoptosis [ 36 , 37 , 48 ]. Herein, we established two study models to specifically determine the effects of ouabain on LSC and LPC death and differentiation using AML KG-1 cells.…”
Section: Discussionmentioning
confidence: 99%